0667 WRIST ACTIGRAPHY IN THE ASSESSMENT OF HYPERSOMNIA. (28th April 2017) - Zeidler, MR; Oldenkamp, C; De Cruz, S; Alessi, CA; Ancoli-Israel, S; Badr, M; Littner, M; Jouldjian, S; Mitchell, M; Martin, JL
Abstract: Introduction: Hypersomnia is a common presenting symptom among patients in sleep disorders centers. The most commonly used clinical tools to assess hypersomnia are patient-completed questionnaires and laboratory multiple-sleep latency tests (MSLT). This study assessed the construct validity of wrist actigraphy for the quantification of hypersomnia severity. We hypothesized that actigraphically assessed daytime sleep parameters (i.e., total daytime minutes and % time asleep) would predict mean sleep onset latency (SOL) on the MSLT. Methods: 17 adult patients referred to the UCLA sleep disorder center who required an overnight sleep study were enrolled. Those with significant neurologic or psychiatric disorders, suspicion of parasomnias or taking sedatives or stimulants were excluded. Subjects completed the Epworth Sleepiness Scale (ESS) and Pittsburgh Sleep Quality Index (PSQI) and wore an actigraph and completed a sleep diary for one week prior to the MSLT. Correlation coefficients relating actigraphically-derived (daytime and nighttime minutes and % time asleep) to mean sleep onset latency on the MSLT were computed. Results: Mean age 44 ± 19 years, 59% male, mean ESS 11.5 ± 5.7, mean MSLT SOL 10.1 ± 4.7 minutes. Wrist actigraphy showed total night time sleep 440 ± 63 minutes, diary night time sleep was 437 ± 81 minutes and PSQI night time sleep was 451 ± 124 minutes. Both actigraphically and diary measured night time sleep were significantly correlated with MSLT SOL (p's <.0.03, r's >0.53) but PSQI night sleep was not (r=0.26, p=.31). Actigraphy daytime sleep was 154 ± 113 minutes; and diary reported day time sleep was 30 ± 31 minutes. Neither of these were correlated with mean MSLT-SOL (p's≥.27, r's ≤ .28). Conclusion: Actigraphy total sleep time may be useful in describing insufficient sleep prior to MSLT; however, actigraphy assessed daytime sleep may not be a substitute for MSLT in patients presenting to sleep disorders clinics. Additional work is needed to determine the utility of wrist actigraphy in the assessment of hypersomnia and whether it is an optimal way to capture habitual sleep prior to an MSLT. Support (If Any): American Sleep Medicine Foundation Strategic Research Award 107-SR-13.